Description of four new species of the spider genus Euryopis Menge, 1868, with new records from Brazil (Araneae, Theridiidae, Hadrotarsinae) - Rodrigues, Everton Nei Lopes; Marta, Kimberly S.; Figueiredo, Cassiano P. (Zootaxa, 2021)
The spider genus Euryopis Menge, 1868 (Theridiidae) currently comprises 76 described species worldwide and only two described species from Brazil and none for Bolivia. In this paper four new species of Euryopis from Brazil and Bolivia are described and illustrated: Euryopis candiota n. sp.; Euryopis nasuta n. sp.; Euryopis catarinensis n. sp. all from Brazil and Euryopis boliviensis n. sp. from Bolivia. New records from Brazil are provided for E. camis Levi, 1963 and E. spinifera O. Pickard-Cambridge, 1895.